Poor people’s Bastilles and democracy’s prisons: a reflection about a “trade-off” between liberty and (self-)control - Melossi, Dario (Tempo Social, 2020)
This essay intends to analyze the relationship between class struggle and prison from two dimensions in modern societies: as a repressive mechanism that operates against political vanguards and as a mechanism that produces discipline over broad social strata, more specifically the dispossessed classes. To fulfill this objective, we use the image of the traditional Bastille, to illustrate the first dimension, and the poor people’s bastilles, to refer to the second. Poor people’s bastilles were constituted as a means of anthropological transformation of the people strongly linked to an idea of democracy as self-government. The self-control to be acquired in prison was inherently tied to the self-government of democracy, as in a “trade-off”. This was the case in the elaboration of the Enlightenment, from seventeenth-century Quakers to Beccaria to Bentham’s Panopticon. The case of the USA is exemplary in this sense, as it allows us to understand the relationship between self-control, inscribed in the project of prison discipline, and self-government, as the free exercise of political citizenship.